Atividade antifúngica in vitro do óleo essencial de cymbopogon nardus L. Rendle (citronela) e do fitoconstituinte citronelal sobre cladosporium carrionii - Paula, Camila Gurgel Dantas de (2015)
Dematiaceous, demaceous or dark fungi comprise a large, heterogeneous group of fungi that cause a variety of diseases, including feohifomycoses, cromoblastomycoses, mycetoma and allergies. Species of the genus Cladosporium are relevant in developing cromoblatomycoses, and stand out as plant contaminants. The toxicity of conventional antifungal and increased resistance to therapeutic regimens, driving the study of the antifungal activity of new alternatives, including natural sources. Given this context, the aim of this study was to evaluate the In vitro antifungal activity of seven essential oils (Laurus nobilis L., Mentha arvensis, Mentha X piperita L., Mentha spicata, Ocimum basilicum L., Cymbopogon nardus L. Rendle e Origanum vulgare) and the phytoconstituent citronellal on strains of dematiaceous fungi. In this study, the following methods were used: microbiological screening, determining the minimum inhibitory concentration (MIC) and Minimum Fungicidal Concentration (MFC), kinetics of microbial death, inhibition of conidial germination and evaluation of morphological changes. Among the essential oils tested, the C. nardus essential oil demonstrated potent antifungal activity, inhibiting the growth of 83,3% of strains used. The Cymbopogon Nardus L. Rendle (citronella grass) belongs to the family Poaceae, subfamily Panicoideae. The Cymbopogon genus consists of eighty-five species. C. nardus presents constitution of essential oil with two major compounds: the citronellal and geraniol. Citronellal is a monoterpene, predominantly formed by the secondary metabolism of plants. The essential oil of C. nardus had its MIC and MFC established at 64 mg / mL and the citronellal in 32 mg / mL. Both the essential oil of C. nardus as citronellal significantly inhibited the radial mycelial growth of the tested strains, the MIC concentrations, MICx2 and MICx4 after 12 days of exposure. In MIC50 concentrations (64 ug / ml- essential oil and 32μg / ml -citronellal) and MIC90 (128 ug / ml - 512μg essential oil and / ml - citronellal), were able to significantly inhibit the germination of fungal conidia from both strains tested. The determination of the effect of the essential oil of C. nardus and citronellal on the morphogenesis of C. carrionii strains showed that both were capable of inducing morphological changes, as development tortuous hyphae, fine and decreased conidiation in MIC concentrations, MICx2 and MICx4. Thus, it is concluded that the essential oil of C. nardus and its phytoconstituent citronellal showed pronounced antifungal activity against the strains of C. carrionii tested, what drives the study of its In vivo antifungal activity, as well as the search for pharmaceutical formulations to be used for the therapy of certain mycoses, especially those caused by dematiaceous fungi.